Role of Multimodality Intraoperative Neurophysiological Monitoring during Embolisation of a Spinal Cord Arteriovenous Malformation: A Paradigmatic Case - Sala, F. (Centauro S.r.l., 2000)
The decision whether or not to embolise during endovascular procedures for arteriovenous malformations (AVMs) of the spinal cord under general anesthesia, relies primarily on neurophysiological results of provocative tests with Lidocaine and short-acting barbiturates. Because of the complex haemodynamics of spinal AVMs, when either sensory (CSEPs) or muscle motor evoked potentials (mMEPs) are used independently, they can mislead the interpretation of provocative tests. This report illustrates the specific but complementary role played by provocative tests using CSEPs and mMEPs during embolisation of a low thoracic spinal cord AVM. We present the case of a 46 year old male with six year history of right lower extremity weakness. At that time, Magnetic Resonance (MR) imaging of the spine disclosed an intramedullary AVM at Til. He remained neurologically stable up to seven months before admission, when he developed sudden onset of low back pain, followed by progressive paraparesis, numbness in lower extremities, urinary retention and fecal incontinence. A new MR imaging study indicated venous thrombosis of the AVM. A two-stage embolisation was performed. During the first procedure, after provocative tests did not affect either CSEPs or mMEPs, an embolisation was performed through a sulcocommisure feeder from the anterior spinal artery (ASA) at T9. Conversely, provocative tests with Lidocaine performed from a right posterior spinal artery (PSA) feeder to the AVM nidus resulted in a significant (>50%) decrease of CSEPs, while mMEPs remained unchanged. The repeatedly positive tests warranted further investigation of the vascular anatomy which disclosed a normal right PSA distal to the nidus; the distal normal PSA was protected with coils. A repeated Lidocaine test was negative and the posterior feeder was embolised with no subsequent changes in CSEPs or mMEPs. After the procedure, the patient experienced only a mild transitory increase in right leg numbness, but no additional motor deficits. Five days later, the embolisation through the ASA feeder at T9 was completed on the basis of negative provocative tests. No additional neurological deficits were observed. Favoring either CSEPs or MEPs during endovascular procedures in the spinal cord is not justified by a solid scientific background. This case report illustrates that monitoring both CSEPs and mMEPs combined with provocative tests allows the safest and most effective embolisation of spinal cord AVMs under general anesthesia.